Effect of Refrigerant Type and Insulation Thickness on Refrigeration Systems of Land and Sea Vehicles - Dalkilic, Ahmet Selim; Celen, Ali; Cebi, Alican; Wongwises, Somchai (ASSOC MECHANICAL ENGINEERS TECHNICIANS SLOVENIA, 2016)
Vehicles are used in the transportation industry to carry temperature-sensitive goods. In fact, they are designed to bear away perishable cartage at specific temperatures. In this study, the cold rooms of a frigoship, railroad car and truck were designed in order to store foods. In addition, the effect of refrigerants and insulation thickness of the cold rooms' refrigeration systems were taken into consideration. In the analysis, R12, R22 and their alternatives of R134a and R410A were selected as refrigerants flowing in the cycle. The evaporator capacity, the condenser capacity, the compressor work, the refrigerant flow rate and the coefficient of performance (COP) of the designed refrigeration systems for each vehicle were determined. It was observed that R134a and R410A had a slightly lower COP and required higher compressor work than R12 and R22 for a condensation temperature. Frigoship, truck and railroad car cold rooms working with R12 had COP values of 2.24, 2.63 and 3.17, respectively. Moreover, the proposed refrigerant R134a can be used in applications with its COP values of 2.16, 2.51 and 3.15 for frigoship, truck and railroad cold rooms, respectively. The influence of the insulation thickness of the wall on evaporator capacity was also investigated. It was observed that the cooling load of the frigoship, railroad car and truck cold rooms decreased 69 %, 68 % and 43 %, respectively, with increase of insulation thickness of the wall from 0.03 m to 0.3 m.
Keywords: refrigeration; alternative refrigerants; COP; cold room; insulation; condenser; evaporator; AIR-FLOW; HEAT-TRANSFER; MASS-TRANSFER; FOOD; DESIGN; Engineering